ДИСКУРСДА ТЎЛИҚСИЗ ГАПЛАРНИНГ ПРАГМАТИК АСПЕКТЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In the article, the pragmatic features of expression of incomplete sentences in the two languages are almost the same, and the pragmatic obstacle caused by irregular use or pronunciation is observed in both languages with the help of examples.
Keywords: pragmatics, incomplete sentences, communicative purpose, speech act, discursive activity, illocutionary task, conventional, unconventional, dialogic process, sociopragmatic factor, illocution.